Inhibition Effects of Phenols on Corrosion of Mild Steel in Nitric Acid - RODGE, J.K.; MULEY, M.R.; KULKARNI, D.R.; DESHPANDE, M.N. (Asian Journal of Chemistry, 2010)
Effects of phenols on the corrosion of mild steel in various concentrations of nitric acid have been evaluated. Per cent loss in weight was found increase linearly with increase in acid concentration. Among the phenols used, p-cresol appears to be good inhibitor followed by m-cresol and phenol. 2-Nitro phenol reveals its oxidizing nature as indicated by increased loss in weight when compared with control. In case of naphthols; 2-naphthol seems to be more effective inhibitor as compared to 1-naphthol. An e.m.f. measurements in nitric acid media indicated that they are inversely related to corresponding weight losses. The trend observed in I.E. values is in the order as p-cresol > m-cresol > 2-naphthol > phenol > 1-naphthol > 2-nitro phenol.